Challenges in mechanics of time dependent materials. proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics. Volume 2 : ([2018]) - Unknown
No abstract available